Effects of Copper Sulfate on Productive, Reproductive Performance and Blood Constituents of Laying Japanese Quail Fed Optimal and Sub-Optimal Protein - Abaza, I.M.; Ezzat, W.; Shoeib, M.S.; El-Zaiat, A.A.; Hassan, I.I. (International Journal of Poultry Science, 2008)
A (3X3) factorial design experiment was conducted to study the effect of three levels of crude protein (16, 18 and 20%) and three levels of copper sulfate (0, 100 and 200 mg/kg diet) as a growth promoter on productive and reproductive performances, egg quality, blood serum constituents and economical efficiency of laying quail hens through 8 weeks. A total number of 270 hens and 135 males of Japanese quail at 8 weeks of age with nearly equal body weight and average rate of laying were randomly divided into 9 groups (30 hens and 15 males each). Each group of birds was sub divided into 3 replicates (10 hens and 5 males) and each replicate was housed in one wire cage. The results showed that the layer body weights at 12 or 16 weeks and weight gain at 12-16 and 8-16 weeks of age were significantly increased with increasing crude protein level from 16-18 or 20%, while there were no significant differences between the groups fed 18 and 20% crude protein throughout the experimental intervals and the whole period. Egg number, rate of laying and egg mass of laying quail hens increased with increasing crude protein at levels 16-18 or 20% (except at 12-16 week of age), while insignificant differences were found between the groups fed 18 and 20% crude protein throughout the experimental intervals and the whole period. Addition of copper sulfate at levels of 100 and 200 mg/kg to laying quail diets significantly improved egg number, rate of laying, egg mass and feed conversion ratio except at 8-12 weeks of age as compared with group non-supplemented with copper sulfate during the experimental period. The highest values of body weight and egg mass were recorded with 20 % protein plus 100 mg copper sulfate/kg diet, while, the best values of feed conversion and The highest values of egg number and rate of laying were recorded with 20 % protein plus 200 mg copper sulfate/kg diet from 8-16 weeks of age for quail layer as compared with other treatments. Laying quails hens fed diet contained copper sulfate levels significantly increased hatchability of fertile eggs percentage (except at 12 wks of age) as compared with those un-supplemented group. Various levels of crude protein or copper sulfate containing diets did not significantly affect on egg quality parameters, while egg yolk cholesterol was significantly decreased with increased copper sulfate levels. The highest values for total serum protein and serum albumin were recorded with experimental groups fed 18 or 20% protein levels compared with those received 16% protein diet, while serum cholesterol values were significantly decreased with increased crude protein. However, dietary copper sulfate supplementation reduced serum tri-glycerides, total cholesterol and low density lipoprotein cholesterol, but increased serum high density lipoprotein cholesterol. The best value of economic efficiency was recorded with laying quail hens fed 18% protein with 100 mg copper sulfate/kg diet compared with other treatment groups.